THE APPLICATION OF PEATY MINERAL SOIL WATER IN IMPROVING THE ADAPTABILITY OF BLACK SOYBEAN TOWARD ALUMINIUM STRESS ON TIDAL MINERAL SOIL WITH SATURATED WATER CULTURE - Hesti Pujiwati; Munif Ghulamahdi; Sudirman Yahya; Sandra Arifin Aziz; Oteng Haridjaja (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
Soybean development in mineral soils of tidal land is hindered by aluminum toxicity. Modification of growing environment and the use of tolerant variety are feasible alternatives. Experiment was conducted with several objectives (1) to identify growth and yield of black soybean at depths of water table, (2) to identify growth and yield of black soybean as effected by application of ameliorants, (3) to identify growth and yield of black soybean, (4) to identify interaction between depth of water table, type of ameliorant, and black soybean variety. The experiment was mineral soils with watershed B type of tidal land in South Sumatera on May to August 2014. Factors investigated were depth of water table (10 and 20 cm), (Tanggamus – as control, Cikuray, Ceneng) and ameliorant type (river water, peaty mineral soil water, and high-tide water). These factors were arranged in a Split-plot Design.The results demonstrated that, for growing black soybean, soils with water table depth of 20 cm was better than those of 10 cm, peaty mineral soil water ameliorant was better than river water or high-tide water ameliorant, Ceneng produced higher yield, but not to those of Cikuray. There was no interaction between surface water depth, ameliorant and variety.